Antibacterial and Antioxidant Activity of Honey Trigona Sp in North Lombok District - Erwan, Erwan; Wiryawan, ‪I Komang Gede; Syamsuhaidi, Syamsuhaidi; Purnamasari, ‪Dwi Kusuma; Sumiati, Sumiati; Muhsinin, ‪Muhammad (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2022)
Honey is known to contain several chemical compounds that have functions as an antibacterial, anti-inflammatory, wound healing, anticancer, and antioxidant. Honey has antibacterial effectiveness against S. aureus, S. typhi, and E. coli bacteria and has high antioxidant levels. This study focused on exploring the antibacterial and antioxidant activity of Trigona sp honey cultivated in North Lombok Regency, NTB, and Apis cerana and Apis dorsata honey as comparisons. The results showed that the three types of honey had antibacterial activity by forming various inhibition zones. These results also show that Trigona, A. cerana and A. dorsata honey are very potential to be consumed for various purposes, especially to improve health and immunity during the Covid-19 pandemic.